2001
DOI: 10.1152/ajprenal.00050.2001
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischemic injury results in permanent damage to peritubular capillaries and influences long-term function

Abstract: Acute episodes of severe renal ischemia result in acute renal failure (ARF). These episodes are followed by a characteristic recovery and repair response, whereby tubular morphology and renal function appear completely restored within approximately 1 mo. However, the chronic effects of such an injury have not been well studied. Male rats were subjected to 60-min bilateral ischemia followed by reperfusion, yielding a characteristic injury. Postischemic animals manifested severe diuresis, peaking at 1 wk postinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
188
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 406 publications
(196 citation statements)
references
References 36 publications
7
188
0
1
Order By: Relevance
“…8,55,56 Capillary rarefaction after kidney injury has been described in a variety of experimental animal models, and in human beings with CKD the decrease of renal capillary density correlates with the severity of fibrosis (Fig. 3).…”
Section: Pericytes and Capillary Rarefaction After Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…8,55,56 Capillary rarefaction after kidney injury has been described in a variety of experimental animal models, and in human beings with CKD the decrease of renal capillary density correlates with the severity of fibrosis (Fig. 3).…”
Section: Pericytes and Capillary Rarefaction After Kidney Injurymentioning
confidence: 99%
“…3). 5662 Basile et al 55 previously used silicone rubber injection to show that rats develop a signi-ficant reduction of peritubular capillary density in kidney (cortex, -25%-30%; inner stripe outer medulla, -35%-40%) at 4 to 40 weeks after IRI. Horbelt et al 58 subsequently identified endothelium by immunostaining postischemic mice and also reported a 45% decrease of microvascular density at 30 days after IRI.…”
Section: Pericytes and Capillary Rarefaction After Kidney Injurymentioning
confidence: 99%
“…One possible mechanism relates to the reduction in peritubular capillary density that persists following the otherwise uneventful recovery from AKI [112]. Our laboratory demonstrated that there was a 30-50% reduction of PTC density which was present following the resolution of GFR, RBF and tubular morphology, at 4 weeks post I/R in rats [112, 113]. Similar results have been reported in other species such as mice [114], and in human kidneys following recovery from delayed graft function [115, 116].…”
Section: Endothelial Involvementmentioning
confidence: 99%
“…Regardless of the mechanisms of dropout, PTC rarefaction post-AKI appears to be permanent [112] suggesting that the intrinsic regenerative capacity of renal capillaries is profoundly limited. This impaired regenerative response may stem in part from a lack of trophic support following AKI.…”
Section: Endothelial Involvementmentioning
confidence: 99%
“…31 A compromised microvascular density may exacerbate the initial hypoxia and potentially contribute to the progressive development of interstitial fibrosis as in the fibrotic scarring observed in Alzheimers disease. 32 According to the “chronic hypoxia hypothesis”, capillary rarefaction is an important factor driving a final common pathway to end stage renal disease.…”
Section: Brief Overview Of Cellular Responses After Ischemic Akimentioning
confidence: 99%